التلوث الثقافي وعلاقته بالمناخ الأسري لدى عينة من طلبة الجامعة - إسماعيل العبيدي, عفراء إبراهيم خليل (Sciences de l'Homme et de la Société, 2013)
استهدفت الدراسة التعرف على الثلوث الثقافي عند طلبة الجامعة، المناخ الأسري عند طلبة الجامعة، دلالة الفرق في متغير التلوث الثقافي  ومتغير المناخ الاسري عند طلبة الجامعة وفقا( للجنس والتخصص الدراسي). طبيعة العلاقة الارتباطية بين المناخ الأسري والتلوث الثقافي عند طلبة الجامعة. توصلت الدراسة إلى: إن طلبة الجامعة لديهم مستوى مرتفع من التلوث الثقافي وان المناخ الأسري الذي يعيشون فيه غير سوي كما أظهرت نتائج الدراسة إن مستوى التلوث الثقافي لدى الذكور أعلى موازنة بالإناث، بينما لم تظهر فروق بين الذكور والاناث في المناخ  الاسري، كما بينت نتائج الدراسة عدم وجود فروق بين الطلبة ذوي الاختصاص الدراسي العلمي والإنساني في التلوث الثقافي والمناخ الأسري، فضلاً عن وجود علاقة ارتباطيه بين المتغيرين.    The study aimed to identify: cultural lilut when university students , Family climate at the university students , Significant difference in the cultural variable pollution and climate variable family when university students in accordance with (sex and area of study), The nature of the correlation between domestic climate and cultural pollution when university students.             The study found: The university students have a high level of pollution, cultural and climate household in which they live is only as study results showed that the level of pollution cultural males higher budget females, while it did not show differences between males and females in a climate of family, also showed the results of the study no differences between students with scientific and academic competence in the cultural pollution of humanitarian and family climate, as well as a correlation between the two variables.